2020
DOI: 10.26480/bda.02.2020.47.51
|View full text |Cite
|
Sign up to set email alerts
|

Land Use Land Cover Classification and Wheat Yield Prediction in the Lower Chenab Canal System Using Remote Sensing and Gis

Abstract: Reliable and timely information regarding area under wheat and its yield prediction can help in better management of the commodity. The remotely sensed data especially in combination with Geographic Information System (GIS) can provide an important and powerful tool for both, land use land cover (LULC) classification and crop yield prediction. The study objectives include LULC classification and wheat yield prediction. The study was conducted for Rabi Season from Nov. 2011 to April 2012, in the command area of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…As a solution, numerous previous studies have shown the contribution of satellite imagery to wheat yield estimation at larger regions, since satellite images provide precise and continuous information on the phenological status. In this regard, various satellite sensors, e.g., Advanced Very High Resolution Radiometer (AVHRR) [8], Moderate Resolution Imaging Spectroradiometer (MODIS) [1,2,8,9], Sentinel-2, Landsat 8 [2], Landsat TM [10,11], IRS-LISS III [12], Indian geostationary satellite INSAT 3A CCD and IRS (Indian Remote Sensing Satellite) [13], Huan Jing (HJ) satellite HJ1A/B and Landsat 8 Operational Land Imager (OLI) [14], etc., have been used for crop yield prediction in the literature. The most widely used satellite sensors for crop yield prediction provide low spatial resolution and high temporal resolution to capture crop phenological development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a solution, numerous previous studies have shown the contribution of satellite imagery to wheat yield estimation at larger regions, since satellite images provide precise and continuous information on the phenological status. In this regard, various satellite sensors, e.g., Advanced Very High Resolution Radiometer (AVHRR) [8], Moderate Resolution Imaging Spectroradiometer (MODIS) [1,2,8,9], Sentinel-2, Landsat 8 [2], Landsat TM [10,11], IRS-LISS III [12], Indian geostationary satellite INSAT 3A CCD and IRS (Indian Remote Sensing Satellite) [13], Huan Jing (HJ) satellite HJ1A/B and Landsat 8 Operational Land Imager (OLI) [14], etc., have been used for crop yield prediction in the literature. The most widely used satellite sensors for crop yield prediction provide low spatial resolution and high temporal resolution to capture crop phenological development.…”
Section: Introductionmentioning
confidence: 99%
“…VIs refers to the values which are often computed from reflectance or radiance of specific bands of satellite images, mostly in the visible and near-infrared bands. Accordingly, researches have been carried out on using indices, such as NDVI [2,11,17], accumulated NDVI [9], adjusted maximum NDVI (MA-NDVI) [1], peak NDVI [4], soil adjusted vegetation index (SAVI) [2], modified SAVI (MSAVI) [2], enhanced vegetation index (EVI) [2], normalized difference drought index (NDDI), normalized difference water index (NDWI), vegetation condition index (VCI), temperature condition index (TCI), vegetation health index (VHI), normalized multi-band drought index (NMDI), visible and shortwave infrared drought index (VSDI), and vegetation supply water index (VSWI) [18] to predict crop yields. Two bands offered by Sentinel 2 from the NIR range, B8 and B8A, can be used for the calculation of the NDVI index.…”
Section: Introductionmentioning
confidence: 99%